2016
DOI: 10.25215/0302.108
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Suicidal Ideation among Older Adults of Kashmir

Abstract: The present study was undertaken to map the ground trends of depression and suicidal ideation among elderly Kashmiris in association with connected socio-demographic variables and also to find the relationship of depression with suicidal ideation. The sample consisted of 184 older adults (102 elderly males & 82 elderly females) taken from different districts of Kashmir. The age of the sample group ranged from 58-76 years with mean age of 67 years. Purposive sampling technique was used for research purpose.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Suicidal ideation. The assessment of suicidal ideation was conducted utilizing the Beck Suicidal Ideation Scale (BSI), a widely recognized instrument in both clinical settings and research domains [31,32]. The BSI's Chinese adaptation, known as the BSI-CV, demonstrated robust reliability and validity in studies involving university populations [33,34].…”
Section: Methodsmentioning
confidence: 99%
“…Suicidal ideation. The assessment of suicidal ideation was conducted utilizing the Beck Suicidal Ideation Scale (BSI), a widely recognized instrument in both clinical settings and research domains [31,32]. The BSI's Chinese adaptation, known as the BSI-CV, demonstrated robust reliability and validity in studies involving university populations [33,34].…”
Section: Methodsmentioning
confidence: 99%
“…In this context, Arora and Rege (2022) argue for the establishment of healthcare facilities specifically designed for women who have experienced violence and elucidate the potential of mental health assistance to dissuade such individuals from taking their own lives. In a survey on working women, Begum and Khokhar (2019) reported that the incidence of suicidal ideation is more prevalent among women employed in the private sector compared to those in the public sector.…”
Section: Indian Women and Suicidementioning
confidence: 99%
“…Suicide ideation, which comprises suicidal thoughts or threats devoid of action, is more common than suicide attempts and completed suicides, and its prevalence varies widely. The lifetime prevalence of suicidal ideation has been reported to range from 2% to 18% ( 16 ).…”
Section: Introductionmentioning
confidence: 99%